Blocking Interstate Natural Gas Pipelines: How to Curb Climate Change While Strengthening the Nation’s Energy System - Bressler, Jason (Columbia Journal of Environmental Law, 2019)
Over the past decade, the growth of natural gas, propelled by the fracking boom, has played a pivotal role in meeting the nation’s ever-expanding energy needs. Simultaneously, it has helped lower energy costs, reduce greenhouse gas emissions, and diminish dependence on foreign energy. Despite these benefits, and the fact that the United States has an abundance of extractable natural gas, the future of this resource as a solution to the nation’s energy demand remains uncertain. This uncertainty is largely attributable to the roadblocks preventing the development of interstate natural gas pipelines—the safest and most efficient means of transporting natural gas. The most formidable roadblock to the construction of interstate natural gas pipelines is Section 401 of the Clean Water Act (“Section 401”), which gives states the power to block construction of any pipeline that may interfere with their water quality standards. States’ use of this “veto” power has escalated in recent years, in what appears to be an attempt to reduce carbon emissions and curb climate change. This escalated use of Section 401 has led to widespread gridlock of pipeline construction, large quantities of unutilized natural gas, and a suboptimal energy system. This Note proposes legislation that would prevent states from blocking construction of interstate natural gas pipelines within their borders without first showing that a more cost-effective alternative for supplying the energy exists. Determining the cost-effectiveness of a project requires consideration of all costs, including the environmental damage, associated with the project. To ensure that these costs, specifically those associated with climate change, are adequately accounted for, each analysis must incorporate the Social Cost of Carbon (“SCC”). In so doing, the SCC should be valued by the states, since the federal figures have been severely devalued by an Executive Order issued by President Trump in March 2017. Part I of this Note provides background on the statutes involved in the construction of interstate natural gas pipelines. It also discusses the purpose of, and the controversy surrounding, the SCC. Part II examines how the courts of appeals and Federal Energy Regulatory Commission (“FERC”) have responded to the states’ increasing use of Section 401 to block interstate natural gas pipelines. It then discusses President Trump’s Executive Order devaluing the federal SCC and explores the various ways in which states have incorporated the SCC into their own energy policies. Finally, Part III argues that states should no longer be permitted to veto interstate natural gas pipelines by withholding water quality certification, but only by showing there is a more cost-effective means of supplying the energy, as determined through cost-benefit analyses that incorporate a state-valued SCC.